READING ALOUD ANECDOTES: INVESTIGATING THE PHONOLOGICAL FEATURES OF SEVENTH-GRADE EFL STUDENTS - Nurmaliana Sari Siregar; Fitri Ani (VISION, 2026)
This study focuses on phonology is uttered by the students grade 7. Phonology refers to study how sounds are organized and used in natural languages. It also expands about the abstract system and patterns of those sounds within a specific language. It looks at the "rules" of how sounds interact and change when put together.To make it clear, this study reveals that the sample, specially for students in grade 7 taking by randomly and they have to read the anecdote story. Most of them still lack in the word of countries [k ʌntris], wearing[w ærin], same [seim], clothes[kl ədz], difficult [di;fik əlt], whether[w əde;r], gentleman [dj əntlm ən], Washington [Wasin tən], tired [t ærd], down [daun]. It happens because they are rarely to practice and applied in daily activity. Phonology research proves that these speech patterns are highly structured, rule-governed, and logical systems. This shifts the educational paradigm. Teachers learn to view a student's speech not as "broken English," but as a highly organized linguistic system transferring rules from one language/dialect to another